Counting on the Words - Bivins, Jason (Bulletin for the study of religion, 2012)
This paper assesses the status of "evidence" in studies of religion by attending to its epistemological lineages, its tone and genre, and its sometimes unconscious methodological presumptions. Exploring the implications of authorial constructions of evidence and the inevitability of our complicity in deciding what counts as "religion," this piece suggests productive engagements with the limits of "evidence" - rather than the often futile attempts to surpass them - can yield fresh ways of thinking and writing about the field's tricky subject.